2021
DOI: 10.1016/j.brachy.2020.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of outcomes using radiotherapy or brachytherapy after resection of primary adenoid cystic carcinoma in oral and maxillofacial regions

Abstract: We wished to investigate the outcome of surgery combined with external-beam radiotherapy (EBRT) or brachytherapy (125 I seeds) for the treatment of primary adenoid cystic carcinoma (ACC) of the oral and maxillofacial region. Data of patients with primary ACC were reviewed retrospectively. Patients were divided into EBRT and brachytherapy groups. Wide tumor excision was done to achieve negative margins. Standard radiotherapy in the EBRT group was 60 Gy. A treatment-planning system was used to create implantatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Our study showed that both IR and ERBT had good therapeutic effects, which is consistent with the conclusions of other studies. Li et al [45] found that there was no significant difference in local control, control of metastasis to regional lymph nodes, or control of distant metastasis between the IR and ERBT groups. In the retrospective comparison case series, the clinical records of 27 patients with primary LGACC and 8 patients with recurrent LGACC were compared, and no statistically significant difference was found in the efficacies of IR and ERBT in terms of distant metastasis rates [16] .…”
Section: Discussionmentioning
confidence: 98%
“…Our study showed that both IR and ERBT had good therapeutic effects, which is consistent with the conclusions of other studies. Li et al [45] found that there was no significant difference in local control, control of metastasis to regional lymph nodes, or control of distant metastasis between the IR and ERBT groups. In the retrospective comparison case series, the clinical records of 27 patients with primary LGACC and 8 patients with recurrent LGACC were compared, and no statistically significant difference was found in the efficacies of IR and ERBT in terms of distant metastasis rates [16] .…”
Section: Discussionmentioning
confidence: 98%